VALORISATION OF SHELL OF INVASIVE CRAYFISH FROM DANUBE RIVER (FAXONIUS LIMOSUS): PROTEIN EXTRACTION AND CHARACTERIZATION - Hromiš, Nevena; Popović, Senka; Šuput, Danijela; Pantić, Jovana; Rakita, Slađana; Tomičić, Zorica; Čabarkapa, Ivana (Food and Feed Research, 2024)
In order to deal with invasive crayfish Faxonius Limosus impact on the native crayfish, as well as fish biodiversity in the Danube River, possible solution would be to find and adopt mechanisms for its utilizing for novel valuable products production. Apart from utilizing edible part for novel food products, shell can be also considered as a source of valuable compounds. Complex structure of shell is mainly composed of three basic compounds: chitin, protein and minerals-mainly calcium carbonate. In this paper, shell proteins were extracted using three extraction methods. The first method was to use naturally present enzymes (proteases and lipases) in crayfish wastes and recover proteins using autolysis process. To accelerate the process, UV radiation was used. Remaining two extraction methods were alkaline extraction of proteins, where in one method alkaline extraction was applied directly to the shell and in the other method alkaline extraction followed the step of acidic demineralization of the shell. Obtained protein concentrates were analyzed for yield, crude protein content, DPPH radical scavenging ability, amino acidic content and structure.Results have shown that similar percent of protein content was obtained by all three methods: 67-68%, but extraction yield was considerably different. Alkaline deproteinization with or without the step of demineralization resulted in 10 % yield, while UV radiation accelerated autolysis resulted in only 3,41 % yield. Although proteins extraction without using exogenous enzymes or chemicals is very interesting approach, drawback of this approach is low process yield. FTIR spectroscopy revealed secondary structure that was similar in all three concentrates, according to the peak deconvolution, whit autolitic concentrate differing in a lesser extent, having slightly higher share of b sheet structures. DPPH assay revealed high antioxidant activity of the concentrates (72-88 %), probably originating from active peptides derived from proteins and residues of carotenoides led by astaxanthin.